Intermediate financial management - Brigham, Eugene F. , 1930-; Daves, Phillip R. (South-Western, 2010)
Suitable for Intermediate or Advanced Corporate Finance course, this book helps in understanding various conceptual theories and practical skills that lead to stronger financial decisions